Effect of curing age on the compressive strength of petrovege blocks - Johnson, O.A. (Trans Tech Publications Ltd, 2014)
In the recent years there has been an intensification of policies on sustainable construction materials in the construction industry. This environmental policy has brought about development of various sustainable materials in which Petrovege blocks is one of the outstanding products. This paper investigates the effect of curing age on the compressive strength of the product. Block samples were prepared by adding 8, 9, 10, 11, 12, and 13 liquid content of the mixture of vegetable oil and crude oil sludge as a binder after the optimum liquid content has been established. The specimens were cured at different period of time of 48hrs, 72hrs, 96hrs, and 120hrs. Mechanical properties of the products were evaluated. Compressive strength of Petrovege samples varies from 5.31 N/mm2 to 18.88 N/mm2 indicating that the compressive strength increases with increase in curing age, while decrease in porosity leads to increased compressive strength for the stipulated curing ages. All samples satisfied the minimum requirements in terms of compressive strength, in accordance with all available standards. Â© (2014) Trans Tech Publications, Switzerland.